TextGrid – Virtual Research Environment for the Humanities - Heike Neuroth; Felix Lohmeier; Kathleen Marie Smith (International Journal of Digital Curation, 2011)
The TextGrid research group, a consortium of 10 research institutions in Germany, is developing a virtual research environment for researchers in the arts and humanities that provides services and tools for the analysis of text data and supports the curation of research data by means of grid technology. The TextGrid virtual research environment consists of two main components: the TextGrid Laboratory (TextGridLab), which serves as the entry point to the virtual research environment, and the TextGrid Repository (TextGridRep), which is a long-term humanities data archive ensuring sustainability, interoperability and long-term access to research data. To support all stages of the research lifecycle, preserve and maintain research data, and ensure its long-term usefulness, existing research practices must be supported. Therefore the TextGridLab provides common functionalities in a sustainable environment to intensify re-use of data, tools, and services, and the TextGridRep enables researchers to publish and share their data in a way that supports long-term availability and re-usability.